Biochemical and morphological characterization of A2BP1 in neuronal tissue. Issue 10 (6th August 2013) - Hamada, Nanako; Ito, Hidenori; Iwamoto, Ikuko; Mizuno, Makoto; Morishita, Rika; Inaguma, Yutaka; Kawamoto, Sachiyo; Tabata, Hidenori; Nagata, Koh‐ichi
<x xml:space="preserve">Abstract</x> A2BP1 is considered to regulate alternative splicing of important neuronal transcripts and has been implicated in a variety of neurological and developmental disorders. A2BP1 was found in neuronal cells and was analyzed biochemically and morphologically. In this study, we prepared a specific antibody against A2BP1, anti‐A2BP1, and carried out protein expression and localization analyses of A2BP1 in rat and mouse tissues. By Western blotting, A2BP1 showed tissue‐dependent expression profiles and was expressed in a developmental‐stage‐dependent manner in the brain. A2BP1 was detected at high levels in neocortex and cerebellum in the rat brain. Immunohistochemical analyses demonstrated that A2BP1 was highly expressed in differentiated neurons but not in mitotically active progenitor cells in the cerebral cortex during developmental stages. In cortical neurons, A2BP1 had accumulated mainly in the nucleus and diffusely distributed in the cell body and dendrites. In differentiated primary cultured rat hippocampal neurons, although A2BP1 was enriched in the nucleus and diffusely distributed in the cytoplasm, it was found in a punctate distribution adjacent to synapses. The results suggest that in neuronal tissues A2BP1 plays important roles, which are regulated in a spatiotemporal manner. © 2013 Wiley Periodicals, Inc.